Is Pupil Activity Associated With the Strength of Memory Signal for Words in a Continuous Recognition Memory Paradigm? - Oliveira, Jorge; Fernandes, Marta; Rosa, Pedro J.; Gamito, Pedro (Frontiers in Psychology, 2021)
Research on pupillometry has been providing evidence for associations between pupil activity and memory processing. The most consistent finding is related to an increase in pupil size for old items compared to novel items, suggesting that pupil activity is associated with the strength of memory signal. However, the time course of these changes is not completely known, specifically, when items are presented in a running recognition task maximizing interference by requiring the recognition of the most recent items from a sequence of old/new items. The sample comprised 42 healthy participants that performed a visual word recognition task under varying conditions of retention interval. Recognition responses were evaluated with behavioural variables for discrimination accuracy, reaction time and confidence in recognition decisions. Pupil activity was continuously recorded during the entire experiment. The results suggest a decrease in recognition performance with increasing study-test retention interval. Pupil size decreased across retention intervals, while pupil old/new effects were found only for words recognised at the shortest retention interval. Pupillary responses consisted of a pronounced early pupil constriction at retrieval under longer study-test lags corresponding to weaker memory signals. However, pupil size was also sensitive to the subjective feeling of familiarity as shown by a pupil dilation to false alarms (new items judged as old). These results suggest that pupil size is related to the strength of memory signal, but also to subjective familiarity decisions in a continuous recognition memory paradigm.